PERENCANAAN STRATEGIS SISTEM INFORMASI PADA DINAS PARIWISATA KABUPATEN CIAMIS MENGGUNAKAN METODE WARD AND PEPPARD - Rohayati , Tuti; Agustin , Mutiara Ayu; Mulyana, Dadan (Universitas Majalengka, 2025)
Ciamis Regency has great tourism potential, but its management is still hampered by an unintegrated information system, limited human resources, and suboptimal IT infrastructure. These conditions affect services, destination promotion, and data-based decision-making. This study aims to design a strategic information system plan for the Ciamis Regency Tourism Office using the Ward and Peppard method to align with business objectives and support technology-based tourism. The study was conducted through an analysis of the internal and external business environment and an IS/IT analysis using SWOT, Value Chain, PEST, Critical Success Factors (CSF), and McFarlan Strategic Grid tools. Data were obtained through observation, interviews, literature studies, and questionnaires. The results of the study produced an information system strategy in the form of a portfolio of 15 applications classified into the McFarlan Grid: Strategic (SI Development and Promotion of Creative Economy, Integrated Tourism SI, VR Tourism Application, Cultural Heritage and Local Destination GIS), 3 High Potential applications, 4 Key Operational applications, and 4 Support applications. A five-year implementation roadmap (2025–2029) was compiled. This planning is expected to address system fragmentation, increase destination competitiveness, and realize Ciamis as a technology-based tourist destination.